the Study of the Physical and Chemical Properties of Moringa Leaf Flour from the Drying of Incandescent Lamps: Kajian Sifat Fisika dan Kimia Tepung Daun Kelor (Moringa oleifera) Hasil Pengeringan Lampu Pijar - Al Firdausiyah, Maula Tuffah; Hariono, Budi (Politeknik Negeri Jember, 2024)
The Moringa plant is known as the Miracle Tree or the Magic Tree because it has great health benefits. Alternative processing of Moringa plants into products such as flour from Moringa leaves is important for further research. One of the critical processes in the manufacture of Moringa leaf flour is the drying process with an incandescent lamp. This research method uses two factors. The first factor is the drying temperature, which consists of 50 °C, 60 °C, and 70 °C with a drying time of 5 hours. The second factor is blanching, which consists of blanching (for 3 minutes at 85°C) and without blanching. The results showed that the interaction between variations in drying temperature and blanching factor was significantly different for water absorption, fineness modulus, moisture content, and ash content.